BPUPKI dan proses perumusan pancasila sebagai dasar negara - Azis, Muhammad Amirul (Maliki Interdisciplinary Journal, 2025)
This study examines the formulation process of Pancasila as the foundational ideology of the Indonesian state through the historical sessions of BPUPKI in 1945. Using a qualitative approach with historical methods, the research explores the dynamics of discussions among national leaders in defining philosophical and ideological principles for a newly independent nation. The findings show that the emergence of Pancasila was the result of profound dialogue and political compromise, reflecting the diversity and pluralism of Indonesian society. The removal of the seven words in the Jakarta Charter and the adoption of the phrase “Belief in One God” represent a strategic effort to maintain national unity. This study concludes that Pancasila serves not only as the state’s ideological foundation but also as a moral, ethical, and cultural compass for Indonesian society. The results are expected to enhance understanding of Pancasila's significance and encourage its consistent implementation in national life.